2005
DOI: 10.1007/bf03166345
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-peptide interaction studied by PELDOR and CW ESR: Peptide conformations and cholesterol effect on the spatial peptide distribution in the membrane

Abstract: Pulsed electron-electron double resonance (PELDOR) combined with continuous-wave electron paramagnetic resonance was used to study inter- and intramolecular dipole-dipole interactions between spin labels for spin-labeled analogs of trichogin GA IV bound to multilamellar membranes of egg L-alpha-phosphatidylcholine (ePC) and in ePC membranes containing cholesterol. All samples were frozen to 77 K. For mono-labeled peptide concentrations in lipid over the range between 0.5 to 2.2 mol%, it is shown that in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Trichogin GA IV is another hydrophobic peptaibiotic, like alamethicin. Its location in the bilayer and its mechanism of action have been studied by EPR and several other spectroscopic and theoretical methods [50,[61][62][63][64][65][66][67][68]. Although the detailed mechanism is still under debate, there is a general consensus that at low P/L ratios, the peptide is monomeric and absorbed parallel to the membrane surface below the polar headgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Trichogin GA IV is another hydrophobic peptaibiotic, like alamethicin. Its location in the bilayer and its mechanism of action have been studied by EPR and several other spectroscopic and theoretical methods [50,[61][62][63][64][65][66][67][68]. Although the detailed mechanism is still under debate, there is a general consensus that at low P/L ratios, the peptide is monomeric and absorbed parallel to the membrane surface below the polar headgroups.…”
Section: Discussionmentioning
confidence: 99%
“…As already stated earlier in the text, inspection of crystallographic data for trichogin GA IV highlights a mixed 3 10 ‐/α‐helix structure for the peptide backbone . Since the α‐ and 3 10 ‐helices exhibit different main‐chain lengths, PELDOR was used to determine the conformation for its membrane‐bound state . Thus, when two TOAC residues are concomitantly incorporated at the ends of the peptaibol, information about its conformation can be obtained from the intramolecular distance between the nitroxide labels.…”
Section: Spin‐labeled Peptaibols: Quaternary Structuresmentioning
confidence: 96%
“…On the other hand, another PELDOR study of O‐Tri in ePC vesicles showed that, over the range of peptide to lipid concentration 0.5–2.2 mol %, trichogin molecules are homogeneously distributed at the inner and outer membranes, whereas upon addition of cholesterol the distribution was found to be inhomogeneous. Therefore, the presence of cholesterol is clearly promoting formation of thermodynamically stable aggregates.…”
Section: Spin‐labeled Peptaibols: Quaternary Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…The distribution of spin-clusters in lipid vesicle membranes can also be assumed to be homogeneous. The dimension of this homogeneous distribution varies from two to three depending on the sample concentration [13][14][15]. This corresponds to a stretched exponential decay function describing the background [16].…”
Section: Introductionmentioning
confidence: 99%